Green manure from pruned biomass affect phosphorus adsorption in soil and its uptake by wheat in Albizia procera based agroforestry system - Prasad, Rajendra; Newaj, Ram; Dar, S.B.; Kumar, Anil; Dhyani, S.K. (Indian Journal of Agroforestry, 2020)
To assess the effect of adding pruned green biomass of Albizia procera Benth. on phosphorus sorption capacity of the soil and uptake of P by trees and wheat intercrop, a study was conducted in a well established 8 years old A. pro cera based agroforestry trial consisting of five treatments viz. control (pure crop), pure tree (without inter cropping), zero pruning+ inter cropping, 50% pruning + inter cropping and 70% pruning + inter cropping. The findings revealed that application of Albizia pruning as green manure significantly reduced P sorption capacity of the soil. Langmuir adsorption maxima and binding energy, and Freundlich P adsorption constants were significantly reduced with application of Albizia pruning. The amount of phosphorus adsorbed by soil at 0.2 mg P/L in solution (standard phosphorus requirement) significantly decreased with addition of increased pruning biomass into soil from zero to 70% pruning treatments. The results also revealed that addition of pruned biomass increased available P in soil. Application of pruned biomass as green manure in 50% pruning + inter cropping and 70% pruning + inter cropping treatments significantly improved the grain yield and P uptake of wheat over zero pruning + inter cropping treatment. However, maximum wheat yield and P uptake in control (pure crop) reflected overriding effect of optimal growth condition in pure crop plot on addition of pruned biomass in pruning treatments. Added pruning had significant effect on P accumulation in 8 years old trees as well as treecomponents. Irrespective of tree-components, on an average, maximum P was accumulated in zero pruning while minimum in 70% pruning. Among the tree components, on an average, maximum P was accumulated in roots followed by branches. The study concludes that addition of Albizia pruning increases P availability through reduced P sorption capacity of soil and recycling of P. Â